2005
DOI: 10.1097/01.brs.0000164119.78463.0c
|View full text |Cite
|
Sign up to set email alerts
|

Centralization: Its Prognostic Value in Patients With Referred Symptoms and Sciatica

Abstract: Patients with sciatica and suspected disc herniation who have a centralization response to a mechanical evaluation will have significantly better outcomes. Patients who do not have centralization will be 6 times more likely to undergo surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
(37 reference statements)
4
35
1
5
Order By: Relevance
“…Although outcome measurements after TESIs showed statistically significant change in leg pain and disability, the differences were not deemed clinically relevant by the patients. These findings are in line with Skytte et al [25] who found that patients with peripheralizing response were six times more likely to undergo surgery than centralizers. Interestingly, the patients who were operated showed higher levels of pain and disablity at intake compared to the non-surgery patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although outcome measurements after TESIs showed statistically significant change in leg pain and disability, the differences were not deemed clinically relevant by the patients. These findings are in line with Skytte et al [25] who found that patients with peripheralizing response were six times more likely to undergo surgery than centralizers. Interestingly, the patients who were operated showed higher levels of pain and disablity at intake compared to the non-surgery patients.…”
Section: Discussionsupporting
confidence: 82%
“…The good outcomes in the centralizing subgroup are in accordance with studies that report good outcomes for centralizers treated with MDT [9,24,25]. The outcomes of the present study justify some optimism, especially when recognizing that all included patients had peripheralizing pain responses, MRI-verified herniated discs that corresponded to clinical assessment and 91% of the patients had chronic symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…2 Posterior tilting of the pelvis has been recommended as an exercise for relief of LBP since at least as far back as the 1980s 3,4 and can still occasionally be found in patient education literature and Internet sites. Nor is the concept unique to this exercise; there are many published examples of directional preference-the identification of which positions and movement patterns relieve or aggravate pain-for lumbar flexion, as well as for extension and lateral bending [5][6][7][8][9][10][11] -and use of that information for therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, a CEN pain response has consistently been associated with good outcome in patients with acute and chronic LBP, 8,13,20,28,29,[35][36][37][38] reflecting a poorer prognosis when CEN is absent.…”
mentioning
confidence: 99%
“…20,27,28 The objective of this study was to investigate the prognostic value of pain response classification at initial physiotherapy examination in patients with LBP who were sick-listed.…”
mentioning
confidence: 99%